What’s in a Label? Propaganda Labels and User Sharing Behavior on Social Media Platforms - Jose, Julia; Geeng, Chris; Morales, Kediel O; McCoy, Damon; Greenstadt, Rachel (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
Authentic information is vital for a society’s ability to make rational decisions. Fabricated and manipulative information can be harmful to society as seen in cases of threatening events that were consequences of foreign propaganda and radical ideologies. While past research has studied dis- and misinformation on social media platforms, the study of propaganda has received much less attention. This study explores the sharing intentions of propaganda on social media platforms and develops an intervention to help detect it. In a randomized controlled trial setting, we added indicators to social media posts that used propaganda techniques to advance an agenda, including techniques that rely on fallacious reasoning, emotional rather than logical reasoning, etc. We then asked our participants (n=1,187) about their intention to engage with these posts. We found that participants were significantly (2.4 times) less likely to share these posts with indicators. We also found that participants’ political affiliation moderated their sharing intentions. We believe our findings provide valuable insights for the study of propaganda on social media platforms.